Zinc oxide nanoparticles synthesised from the Vernonia amygdalina shows the anti-inflammatory and antinociceptive activities in the mice model - Hairui Liu; Peipei Kang; Ying Liu; Yifan An; Yanting Hu; Xiyuan Jin; Xin Cao; Yunfei Qi; Thiyagarajan Ramesh; Xiao Wang (Artificial Cells, Nanomedicine, and Biotechnology)
In this study, we synthesised the zinc oxide nanoparticles from Vernonia amygdalina and evaluated its anti-inflammatory and antinociceptive potentials against the different inflammation and pain induced mice model. The synthesised zinc oxide nanoparticles were characterised by UV, SEM, XRD and FTIR techniques. The anti-nociceptive effects of V. amygdalina were examined by different stimuli e.g. acetic acid, glutamate, capsaicin, and formalin-induced nociception in mice. The anti-inflammatory effects of synthesised zinc oxide nanoparticles were assessed by air sack assessment and the level of inflammatory cytokines were studied. The muscle tension of animals were studied through open field assessment. The present study exhibited proficient antinociceptive and anti-inflammatory actions of the synthesised Zinc oxide nanoparticles from V. amygdalina. The sormulated zinc oxide nanoparticles were appreciably reduced the acetic acid, glutamate, capsaicin, and formalin-induced nociceptive responses in mice. Further the zinc nanoparticles were exhibited the potent anti-inflammatory actions via reducing the inflammatory response and pro-inflammatory cytokines level in the mice. In conclusion, the findings of this study proved the beneficial effects of zinc oxide nanoparticles from V. amygdalina against the different pain and inflammation-induced mice. Hence, it was clear that the zinc nanoparticles from V. amygdalina could be promising antinociceptive and anti-inflammatory agent in the future.